Experimental study of the effect of microspheres and milled glass in the adhesive on the mechanical adhesion of single lap joints. Issue 11 (19th September 2017) - Hunter, R.; Möller, J.; Vizán, A.; Pérez, J.; Molina, J.; Leyrer, J.
ABSTRACT: This article describes several experiments conducted on single lap joints (SLJ) subjected to tensile mechanical loads. Two epoxy adhesives, with slow and fast curing, were used, with a weight of 0%, 3%, and 10% of glass microspheres and milled glass particles, respectively. The adherends used in the construction of the specimens were fiber-reinforced polymers. The types of failures produced in the SLJ specimens were classified according to ASTM standards. The results of the experimental tests on the SLJ with fast-curing epoxy adhesive showed that the use of milled glass and glass microspheres improved the strength of the joint compared with the neat fast-curing epoxy adhesive. As for the experimental test on the joint with slow-curing epoxy adhesive, the results showed that the use of milled glass and glass microspheres decreased its strength when using different additive concentrations compared with the neat slow-curing epoxy adhesive.